Effects of developmental stress on animal phenotype and performance: a quantitative review. (4th January 2019) - Eyck, Harrison J.F.; Buchanan, Katherine L.; Crino, Ondi L.; Jessop, Tim S.
ABSTRACT: Developmental stressors are increasingly recognised for their pervasive influence on the ecology and evolution of animals. In particular, many studies have focused on how developmental stress can give rise to variation in adult behaviour, physiology, and performance. However, there remains a poor understanding of whether general patterns exist in the effects and magnitude of phenotypic responses across taxonomic groups. Furthermore, given the extensive phenotypic variation that arises from developmental stressors, it remains important to ascertain how multiple processes may explain these responses. We compiled data from 111 studies to examine and quantify the effect of developmental stress on animal phenotype and performance from juveniles to adulthood, including studies from birds, reptiles, fish, mammals, insects, arachnids, and amphibians. Using meta‐analytic approaches, we show that across all studies there is, on average, a moderate to large negative effect of developmental stress exposure (posterior mean effect: | d | = −0.51) on animal phenotype or performance. Additionally, we demonstrate that interactive effects of timing of stressor onset and the duration of exposure to stressors best explained variation in developmental stress responses. Animals exposed to stressors earlier in development had more‐positive responses than those with later onset, whereas longer duration of exposure to a stressor caused responses to be stronger in magnitude. However, the high amount of heterogeneity in our results, and the low degree of variance explained by fixed effects in both the meta‐analysis ( R 2 = 0.034) and top‐ranked meta‐regression model ( R 2 = 0.02), indicate that phenotypic responses to developmental stressors are likely highly idiosyncratic in nature and difficult to predict. Despite this, our analyses address a critical knowledge gap in understanding what effect developmental stress has on phenotypic variation in animals. Additionally, our results highlight important environmental and proximate factors that may influence phenotypic responses to developmental stressors.